Медикаментозна корекція гострого панкреатиту в щурів за експериментальних умов = Rats’ experimental acute pancreatitis pharmacological correction - Koshelnik, E. L.; Desyatsky, V. V. (Journal of Education, Health and Sport, 2015)
Koshelnik E. L., Desyatsky V. V. Медикаментозна корекція гострого панкреатиту в щурів за експериментальних умов = Rats’ experimental acute pancreatitis pharmacological correction. Journal of Education, Health and Sport. 2015;5(10):199-206. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32619 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A199-206 https://pbn.nauka.gov.pl/works/661564 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. УДК 591.437:616.37-002-08 МЕДИКАМЕНТОЗНА КОРЕКЦІЯ ГОСТРОГО ПАНКРЕАТИТУ В ЩУРІВ ЗА ЕКСПЕРИМЕНТАЛЬНИХ УМОВ RATS’ EXPERIMENTAL ACUTE PANCREATITIS PHARMACOLOGICAL CORRECTION О. Л. Кошельник, В. В. Десятський E. L. Koshelnik, V. V. Desyatsky Одеський національний медичний університет, Одеса Odessa National Medical University, Odessa Summary Work is dedicated to model of acute pancreatitis and pathological changes of pancreatic tissues of rats with L-arginine-induced acute experimental pancreatitis and morphological tests of therapeutic effects of different forms of dalargin The obtained data indicate that using of free and liposomal forms of dalargin, with therapeutic aims, in conditions of results in processes of macro- and microscopic changes in pancreatic tissue normalization. Efficacy significantly prevails the same of peptide’s free form. This positive effect is the experimental background in clinical use of nitric oxide blocking and liposomal form of dalargin for treatment of acute pancreatitis. Key words: model, acute experimental pancreatitis, morphology, treatment. Резюме Робота присвячена моделюванню та вивченню патологічних змін тканини підшлункової залози у щурів з L-аргінін-індукованим гострим експериментальним панкреатитом, а також морфологічному тестуванню лікувальних ефектів різних форм даларгіну та NG-нітро-L-аргініну за цих умов. Показано, що за умов використовуваної нами моделі ГЕП, індукованого за допомогою дворазової ін’єкції L-аргініну, в тканині ПЗ формуються морфологічні зміни, що характерні для гострого патологічного процесу: запалення, геморагії, некроз. Це підтверджує адекватність використаної нами моделі відповідному клінічному стану. Застосування вільної та ліпосомальної форм даларгіну при L-аргінін-індукованому ГЕП також сприяє нормалізації макро- та мікроскопічних змін в тканинах ПЗ. При цьому ефективність ліпосомальної форми даларгіну в 1,5 раза перевищувала таку у вільної форми пептиду. Отримані дані є експериментальним обґрунтуванням можливого клінічного застосування інгібіторів синтезу окису азоту та ліпосомальних форм опіоїдних пептидів з метою лікування гострого панкреатиту. Ключові слова: модель, гострий експериментальний панкреатит, морфологія, лікування. Резюме Работа посвящена изучению патологических изменений ткани поджелудочной железы крыс с L-аргинин-индуцированным острым экспериментальным панкреатитом, а также морфологическому тестированию лечебных эффектов различных форм даларгина и NG-нитро-L-аргинина. Показано, что в условиях использованной нами модели ГЭП, индуцированного двукратной инъекцией L-аргинина, в тканях поджелудочной железы формируются изменения, характерные для острого патологического процесса: воспаление, геморрагии, некроз. Это подтверждает адекватность использованной нами модели соответствующему клиническому состоянию. Использование свободной и липосомальной форм даларгина также способствует нормализации макро- и микроскопических изменений ткани ПЖ. При этом эффективность липосомальной формы даларгина в 1,5 раза превышала таковую у свободной формы пептида. Полученные данные являются экспериментальным обоснованием целесообразности использования ингибиторов синтеза оксида азота и липосомальных форм опиоидных пептидов в лечебных мероприятиях при остром панкреатите в клинике. Ключевые слова: модель, L-аргинин, острый экспериментальный панкреатит, морфология, лечение.